Changes in concentration of pesticide residues in fruits and vegetables during household processing. (2022) - Naman, Maeena; Masoodi, F.A.; Wani, Sajad Mohd; Ahad, Tehmeena
Abstract: Monitoring of pesticide residues in fruits and vegetables and their processed products like jams, pickles, juices, ketchup, dried products and canned products was undertaken. The study was conducted to assess the effect of washing, peeling, heating and cooking on concentration of various pesticides. The stability of various pesticides in samples and their products was assessed. Pesticide residues were extracted using QuEChERS method and analysed by GC-MS. It was observed that pesticides like mancozeb and carbofuron were found to be stable for tomato and potato while chloropyriphos, captan and mancozeb (in other samples) were found to be unstable. It was also observed that peels and pomace showed highest levels of pesticide residues. In this study, washing, peeling and heat processing (boiling and blanching) have been found to be the most effective ways of pesticide residue dissipation. Graphical Abstract: ga1 Highlights: Food processing; cost effective method for residue dissipation. Processed products fit to be consumed. Pomace and peels have higher content of residue than pulp.